REVERSE PHASE HPLC METHOD FOR QUANTITATIVE DETERMINATION OF EMBELIN IN POLY HERBAL FORMULATION - S.MAHESHWARAN; C.SURESHKUMAR; R. MOHANKUMAR; S. NARASIMHAN (International Journal of Pharma and Bio Sciences, 2013)
Embelin is a unique chemical compound found in nature, composed of quinone moiety resembling Coq10 (Ubiquinones), having ketone and hydroxy groups. A Optimum solvent for extracting embelin from Embelia ribes and its simultaneous determination of content of embelin in the extract and content of embelin in Formulation which is available in market has been done in Gradient HPLC with less runtime of 10 minutes. Satisfactorily the results were obtained with respect to LOQ (0.5ppm), LOD (0.17 ppm) and Linearity (Correlation: 0.9976), Ruggedness (RSD: 0.8%), Accuracy (86%), Precision (RSD: 1.0%). The Present method was sensitive, accurate, simple reproducible and therefore can be recommended for using in Quality control to check the content of Embelin.